AWARENESS ON HAEMOSTATIC DRUGS IN MANAGEMENT OF BLEEDING SOCKETS AMONG DENTAL STUDENTS - Vijaya Kumaran, Ghayathri; Ganapathy, Dhanraj; Kumar, Kiran (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to determine the understanding regarding haemostatic drugs in management of bleeding sockets among dental students. The purpose of this study is to create awareness and determine the understanding of haemostatic drugs in the management of bleeding sockets among dental students. This study was conducted based on a questionnaire that consisted of 10 questions through a web-linked application called Survey Monkey. A convenient sample size of 100 consecutive dental students who are currently practicing in Chennai participated in the study. As an overall result, most of the participants are aware of haemostatic drugs in the management of bleeding sockets. As a conclusion, the awareness of haemostatic drugs in the management of bleeding sockets and their role and development among dental students in Chennai is adequate, but certain knowledge has to be brushed up among them for a higher level. Furthermore, they need to be trained on these grounds to help them treat their patients with more consent and awareness.